The Fornax Cluster VLT Spectroscopic Survey II – Planetary Nebulae kinematics within 200 kpc of the cluster core. Issue 2 (14th March 2018) - Spiniello, C; Napolitano, N R; Arnaboldi, M; Tortora, C; Coccato, L; Capaccioli, M; Gerhard, O; Iodice, E; Spavone, M; Cantiello, M; Peletier, R; Paolillo, M; et al.
Abstract: We present the largest and most spatially extended planetary nebulae (PNe) catalogue ever obtained for the Fornax cluster. We measured velocities of 1452 PNe out to 200 kpc in the cluster core using a counter-dispersed slitless spectroscopic technique with data from FORS2 on the Very Large Telescope (VLT). With such an extended spatial coverage, we can study separately the stellar haloes of some of the cluster main galaxies and the intracluster light. In this second paper of the Fornax Cluster VLT Spectroscopic Survey, we identify and classify the emission-line sources, describe the method to select PNe, and calculate their coordinates and velocities from the dispersed slitless images. From the PN 2D velocity map, we identify stellar streams that are possibly tracing the gravitational interaction of NGC 1399 with NGC 1404 and NGC 1387. We also present the velocity dispersion profile out to ∼200 kpc radii, which shows signatures of a superposition of the bright central galaxy and the cluster potential, with the latter clearly dominating the regions outside R ∼ 1000 arcsec (∼100 kpc).